Evaluation of high-temperature reverse osmosis for recycling boiler blowdown in industrial applications - Joel Minier-Matar (17052378) (2024)
Boilers are key component of industrial plants due to their ability to generate steam to be used in various plant unit processes. As part of boiler's operation, a waste stream is generated, known as blowdown, which is discharged at high temperatures (80-100°C) requiring cooling before treatment and/or disposal. New technologies like high temperature reverse osmosis (HTRO) may have the ability to treat the blowdown at its discharge temperature, allowing the recycle of the hot permeate back to the boilers as makeup water. By recycling the permeate at high temperature, the heat energy in the hot stream is being reused to minimize energy input for boilers. In this study, the feasibility of this novel HTRO application, for direct treatment of real boiler blowdown stream, was evaluated. Lab-scale experiments at temperatures of 35, 60, and 85 °C were conducted using boiler blowdown samples collected from an industrial plant, and the economic benefits were assessed. Results showed an average flux of 30 L/m2h for the RO experiment at 35°C; and 42 L/m2 h at 60 °C. The membrane rejection decreased from 97 % at 35°C to 92 % at 60°C; due to the increase in the diffusivities of ions at higher temperatures; however, the permeate quality met the boilers feedwater specifications. A sharp decline in flux was observed at 85°C followed by an increase in turbidity and total organic carbon in the concentrate stream; which may be attributed to polyamide hydrolysis at such high temperatures. In terms of economic benefit, a conventional RO at 35°C will generate a revenue of $1.9/m3permeate, and HTRO at 60°C, $2.8/m3 permeate; mainly due to thermal energy savings. Further investigation into the causes of the flux decline observed at 85°C is recommended to gain the attractive full economic potential for recycling boiler blowdown which is estimated at $3.9/m3 permeate. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2024.106812